Exposure to psychoactive compounds amongst students of medical university - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta (Central European Journal of Public Health, 2017)
OBJECTIVE: The aim of this study was to assess the frequency of exposure to psychoactive compounds amongst students of the Medical University of Bialystok. METHOD: This cross-sectional study included 504 students selected by means of stratified sampling based on the university faculty, study discipline and year, and participant's gender. RESULTS: Nearly three fourths of our respondents have contact with their student colleagues who use psychoactive compounds, or have heard that such individuals exist. Approximately one fourth of the students declared that they considered using psychoactive compounds at least once. Marijuana and hashish were the psychoactive compounds our respondents used most frequently. Median age of the first contact with these substances was 18 years. Alarmingly high fraction of respondents declared that most of psychoactive compounds included in the study is easily available and obtaining them would not take them longer than one day. Furthermore, 15% of respondents admitted to being involved in the distribution of psychoactive compounds. CONCLUSION: The exposure of medical university students to psychoactive compounds represents similar problem as in their peers studying other disciplines. However, in view of its specific consequences (including potential threat to patients' health and life), the problem should not be underestimated.
Keywords: dospělí; Female; Illicit Drugs; zakázané drogy; Adult; Polsko; mladý dospělý; ženské pohlaví; průřezové studie; Adolescent; lidé; Students, Medical; Psychotropic Drugs; studenti lékařství; Cross-Sectional Studies; Male; Young Adult; psychotropní léky; Substance-Related Disorders; mužské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Poland; mladiství; Humans